Competency Approach (CE) and Formative Assessment (EF). Case: Rural school - Quiñones Ramírez, Leonela (2021)
This research was carried out with the objective of analyzing and explaining how the competence approach (CE) and formative evaluation (PE) are developed in rural schools. The qualitative approach was used under the case study design using participant observation technique. The results show that in the development of CE and PE, complex interdisciplinary activities were proposed to develop reasoning, creativity and critical thinking through planning, learning management and evaluation processes. However, some students have not achieved improvements in their learning, despite applying different strategies and previously sharing the evaluation criteria. It was concluded that for thedevelopment of CE and PE, in distance education, it is essential to manage activities in an interdisciplinary way, prioritizing some competences because, due to the communication limitations that exist, it was not possible to work all the areas established in the curriculum. For this, all possible means must be used that allow feedback on the process and the final products.